2006
DOI: 10.1159/000094425
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Injecting and Non-Injecting Illicit Opioid Users in a Multisite Canadian Sample (OPICAN Cohort)

Abstract: Illicit opioid use in Canada and elsewhere increasingly involves a variety of opioids and non-injection routes of administration. Injection and non-injection opioid users tend to differ in various key characteristics. From a public health perspective, non-injection routes of opioid use tend to be less harmful due to lesser morbidity and mortality risks. Our study compared current injectors (80%) and non-injectors (20%) in a multi-site sample of regular illicit opioid users from across Canada (‘OPICAN’ study). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 97 publications
4
39
1
Order By: Relevance
“…Second, a specific examination of those who also used crack, compared with those who did not also use crack, revealed that the former were significantly more likely to be characterized by key indicators of social and health risks or harms, including unstable housing, criminal activity, health problems, and injection risks (110). Finally, a more detailed examination of the current noninjectors in the cohort revealed that most had an injection history and were older, suggesting that they had matured out of drug use by injection (43).…”
Section: Drug Usementioning
confidence: 95%
See 1 more Smart Citation
“…Second, a specific examination of those who also used crack, compared with those who did not also use crack, revealed that the former were significantly more likely to be characterized by key indicators of social and health risks or harms, including unstable housing, criminal activity, health problems, and injection risks (110). Finally, a more detailed examination of the current noninjectors in the cohort revealed that most had an injection history and were older, suggesting that they had matured out of drug use by injection (43).…”
Section: Drug Usementioning
confidence: 95%
“…At the same time, opioid injectors may shift to noninjection forms in search of less risky forms of drug use or as a step in maturing out of their use habits altogether (42). Given the substantially increased levels of risks and harms associated with injection forms of opioid use, both ends of the transition trajectory have enormously important implications for prevention, yet they are little understood or used in interventions (43)(44)(45).…”
Section: Nonopioid Usementioning
confidence: 99%
“…1,2 In both cases, viral transmission occurs mainly through sharing of contaminated syringes. 3,4 In spite of the availability of an extensive syringe exchange network, with access sites situated in the places where they are most needed, 5 Montreal surveillance data have shown an increase in the incidence of HIV from 3.5 cases per 100 person-years between 1998 and 2002 to 4.9 cases per 100 person-years between 2003 and 2006.…”
Section: Introductionmentioning
confidence: 99%
“…school, parties) has also been found to influence the decision to initiate; setting, coupled with peer use and exposure, helps to normalize prescription drug abuse, creating comfort in the perception that use is common and fun [16]. Social and environmental contexts have also been found to contribute to transitions to alternative routes of administration, including drug injecting among established illicit PO users [5,10,17,18].…”
Section: Introductionmentioning
confidence: 99%